14 Trends in call-to-door times for patients with acute ST-elevation myocardial infarction. (June 2018) - Wardak, Fazlullah; Cais, Simon; Hobson, Alex
Abstract : Background: Early reperfusion therapy with primary percutaneous coronary intervention (PPCI) is the cornerstone of treatment for patients with acute ST-elevation myocardial infarction (STEMI), with delays in time to reperfusion leading to increased mortality. 1 2 The ambulance service is involved in taking four out of every five STEMI patients directly to hospital for PPCI. 3 Whilst we make stringent efforts to improve in-hospital delays (door-to-balloon time), delays pre-hospital (call-to-door time) are just as important in terms of patient outcomes. We were concerned that call-to-door times could be increasing due to the current pressures on the Ambulance service and that this could adversely affect the outcome of patients with STEMI. Objective: To analyse temporal trends in call-to-door times in our local area. Methods: From our local primary PCI database we retrospectively identified all patients brought direct to the cardiac catheter lab by our local Ambulance services. Admissions via the emergency department, inter-hospital transfers and inpatients were excluded. Of these we included all patients in whom time of the call and time of arrival were recorded. We identified a total of 1374 patient records from January 2011 through September 2017 for analysis, a period in which there was no change to our catchment area. Results: Mean call to door times have progressively increased over the seven year period from 53 min in 2011 to 78 min in 2017 (a 47% increase, see figure 1). Conclusions: An efficient Ambulance service is an integral part of a successful PPCI service. This study demonstrates a worrying trend in call-to-door times over the last 7 years. Increases in call-to-door times will have adverse effects on outcomes for patients undergoing PPCI for STEMI. This trend is likely to be due to the increasing pressures on the Ambulance service with subsequent relaxing of targets, and increased use of first responders by motorcycle or car with a subsequent need to wait for two person crews. References: Boersma E, Maas AC, Deckers JW, Simoons ML. Early thrombolytic treatment in acute myocardial infarction: reappraisal of the golden hour. Lancet 1996;348: 771–5. . De Luca G, Suryapranata H, Ottervanger JP, Antman EM. Time delay to treatment and mortality in primary angioplasty for acute myocardial infarction: every minute of delay counts. Circulation 2004;109:1223–5. . Weston C, Gavalova L, Whittaker T, Van Leeven R. 2014. Myocardial Ischaemia National Audit Project. Heart attack in England, Wales, and Northern Ireland: Annual Public Report April 2015 – March 2016. NICOR, ed. Padcreative. https://www.ucl.ac.uk/nicor/audits/minap/documents/annual_reports/minap-2015–16–annualreport (accessed 28 Nov 2017).